2022
DOI: 10.1136/bmjopen-2021-056606
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the uptake of asymptomatic COVID-19 lateral flow testing in Birmingham, UK: survey and qualitative research

Abstract: AimTo examine public perspectives on lateral flow testing (LFT) for COVID-19.DesignOnline survey with nested semi-structured interviews.SettingBirmingham, UK.Participants220 Birmingham residents, 21 of whom took part in an interview.ResultsFifty-six per cent of respondents had taken an LFT. Reasons for not testing included adherence to other government COVID-19 guidance, having had a vaccination and not thinking LFTs were accurate. In 16% of households with children nobody, including children, was testing. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Our study indicates that when risk is perceived, people are willing to self-test and are also more likely to comply with expected actions following a positive COVID-19 self-test result. However, unlike in the UK where participants of a mixed-method study expressed willingness to maintain the use of COVID-19 preventive measures after a negative result, 23 half of the respondents in our study would not self-isolate after a negative result even if they had symptoms compatible with COVID-19 and they had been in contact with a COVID-19 case. As in other countries, provision of information on the possibility of false negative results will be needed when self-testing is introduced in Nigeria.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Our study indicates that when risk is perceived, people are willing to self-test and are also more likely to comply with expected actions following a positive COVID-19 self-test result. However, unlike in the UK where participants of a mixed-method study expressed willingness to maintain the use of COVID-19 preventive measures after a negative result, 23 half of the respondents in our study would not self-isolate after a negative result even if they had symptoms compatible with COVID-19 and they had been in contact with a COVID-19 case. As in other countries, provision of information on the possibility of false negative results will be needed when self-testing is introduced in Nigeria.…”
Section: Discussionmentioning
confidence: 67%
“…Nevertheless, the high likelihood of using self-testing observed in our survey should be treated with caution, as the enthusiasm for this case detection approach may be a reflection of discontent with restrictive government policies on testing. It remains to be seen whether COVID-19 self-tests, once regulated and available on the market, are as widely adopted as the present study seem to suggest, or as other study conducted in the United Kingdom—where self-testing is regulated—have reported 23…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The color lines formed in the lateral flow tests can be scaled by the naked eye; therefore, no specific analytical device is needed, resulting in a substantially low price of the assay. The fact that the tests are based on a simple paper or plastic foil cut in combination with a small number of reagents such as antibodies, aptamers, color, luminescence, fluorescence, or nanoparticles labels on the surface is another reason why the lateral flow tests are economically available analytical devices with practical application in various studies [101][102][103][104]. The lateral flow tests have disadvantages as well.…”
Section: Routine Crp Point-of-care Tests and Immunochemical Testsmentioning
confidence: 99%
“…Respiratory sample collection for infection diagnosis can be uncomfortable and testing fatigue is a recognised consequence of the SARS-CoV-2 pandemic. 2 Therefore, simultaneous testing for multiple pathogens on a single sample helps mitigate these challenges. Rapid antigen testing (RAT) for SARS-CoV-2 has been in widespread use in Australia, including home self-testing.…”
mentioning
confidence: 99%